2005
DOI: 10.1007/s10800-005-9069-8
|View full text |Cite
|
Sign up to set email alerts
|

Induced electrodeposition of tungsten with nickel from acidic citrate electrolyte

Abstract: Induced electrodeposition of Ni-W alloys was carried out onto steel substrates from acidic citrate baths (pH 4.5) under different conditions of concentration of electrolyte, current density and temperature. Bright and highly adherent Ni-W deposits were successfully obtained with a relatively high cathodic current efficiency CCE (80-85%). The CCE increases greatly with increasing pH and Ni 2+ ion content in the bath. The W% in the alloy deposits is in the range of 4-20 wt% depending on the operating condition. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…The microstructure of the Ni-W deposits exhibits (111) preferred orientation similar to the fcc (111) phase of Ni. Changing the operating conditions has no significant effect on the XRD patterns [54]; some authors [55,56] have reported the formation of amorphous Ni-W alloys. However, the data shown here cannot be taken as evidence that amorphous alloys have also been deposited.…”
Section: Resultsmentioning
confidence: 99%
“…The microstructure of the Ni-W deposits exhibits (111) preferred orientation similar to the fcc (111) phase of Ni. Changing the operating conditions has no significant effect on the XRD patterns [54]; some authors [55,56] have reported the formation of amorphous Ni-W alloys. However, the data shown here cannot be taken as evidence that amorphous alloys have also been deposited.…”
Section: Resultsmentioning
confidence: 99%
“…The reduction of copper ions, mostly Cu 2+ at low cathodic potentials around −0.5 V in acidic citrate baths was reported recently elsewhere. 21,22 It was also shown that the reduction of Cu-Cit complexes is possible at more negative potentials when the pH of the acidic citrate baths exceeds 3. However, Cu-Cit complexes hardly form in acidic citrate baths of pH below 2.…”
Section: Resultsmentioning
confidence: 99%
“…Interest in the electrodeposition of NiFeW ternary alloys has increased rapidly in recent years because of their excellent properties, such as physical, chemical and mechanical properties. The introduction of tungsten into NiFe alloy coatings improves their microhardness [1][2][3][4][5][6], wear resistance [5][6][7], corrosion resistance [8][9][10] and uniformity organization [11][12][13][14]. There are many studies about the excellent properties of FeW and NiW alloy coatings [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%